Robotic-assisted versus laparoscopic versus open liver resection: comparison of postoperative outcomes according to the IWATE difficulty score - Abdelhadi, Schaima; El-Ahmar, Mohamad; Abbasi Dezfouli, Sepehr; Vedder, Katharina; Hermann, Maike; Orth, Vanessa; Halawa, Mahmoud; Mönnichs, Meik; Reißfelder, Christoph; Şandra-Petrescu, Flavius Ionuţ (Surgical endoscopy and other interventional techniques, 2025)
Background Minimally invasive liver surgery (MILS) has become increasingly established, yet the relative benefits of laparoscopic (LLR) and robotic-assisted liver resection (RLR) compared with open liver resection (OLR) across different levels of surgical difficulty remain debated. This study aimed to compare perioperative outcomes of RLR, LLR, and OLR stratified by the IWATE difficulty score. Methods All consecutive patients undergoing elective liver resection between April 2018 and December 2024 at a high-volume hepatobiliary center were retrospectively analyzed from a prospectively maintained database. Patients were stratified into low/intermediate (IWATE 0-6) and advanced/expert (IWATE 7-12) groups. Multivariable regression and interaction term analyses were performed to adjust for confounders and assess the modifying effect of surgical difficulty. Results A total of 686 patients were included: 425 (62%) underwent LLR, 101 (15%) RLR, and 160 (23%) OLR. Of these, 400 (58%) were advanced/expert resections. Minimally invasive approaches were associated with significantly reduced blood loss, morbidity, and length of stay compared with OLR across all IWATE levels. In advanced/expert resections, RLR provided the greatest benefit, with lower major complications (8% vs. 17% LLR vs. 23% OLR) and shorter length of stay (median 6 vs. 9 days OLR). Multivariable analyses confirmed these findings, with both LLR (OR 0.24, 95% CI 0.10-0.55) and RLR (OR 0.24, 95% CI 0.06-1.00) independently associated with reduced major complications compared to OLR. Interaction analyses demonstrated that the comparative advantage of RLR was most pronounced in advanced/expert resections, while LLR showed particular efficiency in low/intermediate cases. Conclusion Both LLR and RLR are safe and effective across all levels of surgical difficulty. RLR, however, offers distinct advantages in technically demanding advanced and expert cases. These findings reinforce the role of MILS as the preferred standard and highlight the importance of tailoring the surgical approach to case complexity.